What makes a good title?. (December 2013) - Grant, Maria J.
Abstract The chances are the first thing you when you set out to write an article is the title. But what factors transform a mediocre title into a good title? Firstly, it should be both informative and specific, using words or phrases likely to be used when searching for information, for example 'nurse education' rather than simply 'nurse'. Secondly, it should be concise yet convey the main ideas clearly; articles with short titles reporting study findings have been found to attract higher numbers of viewing and citations. Thirdly, provide details of the study design to assist the reader in making an informed choice about the type of project your article is reporting. In taking these small steps when developing your title, your title can present a more concise, retrievable and clear articulation of your article.